Prevalence and Trends of Sexual Behaviors Among Young Adolescents Aged 12 Years to 15 Years in Low and Middle-Income Countries: Population-Based Study - Zhengyue Jing; Jie Li; Yi Wang; Chengchao Zhou (JMIR Publications, 2023)
BackgroundRisky sexual behaviors remain significant public health challenges among adolescents. Nearly 90% of adolescents live in low and middle-income countries (LMICs), but few studies have used standardized methodology to monitor the prevalence and trends of sexual behaviors among adolescents in LMICs. ObjectiveThis study aimed to assess the prevalence of sexual behaviors (ever had sexual intercourse, multiple sexual partners, and condom use) among adolescents aged 12 years to 15 years as well as the trends in prevalence between 2003 and 2017. MethodsFor this population-based study, we used recent data from the Global School-based Student Health Survey conducted in 69 LMICs from 2003 to 2017 to assess the recent prevalence of sexual behaviors by using complex analysis and a random effects meta-analyses method. Using the chi-square trend test, we also assessed the trends in the prevalence of sexual behaviors in 17 countries that had conducted ≥1 round of surveys from 2003 to 2017. ResultsWe included 145,277 adolescents aged 12 years to 15 years (64,719/145,277, 44.5% boys) from the 69 LMICs that had conducted ≥1 survey and 80,646 adolescents aged 12 years to 15 years (34,725/80,646, 43.1% boys) from the 17 LMICs that had conducted ≥1 round of surveys. The recent global prevalence of ever had sexual intercourse was 6.9% (95% CI 6.2%-7.6%) and was higher among boys (10.0%, 95% CI 9.1%-11.1%) than girls (4.2%, 95% CI 3.7%-4.7%) and among those aged 14 years to 15 years (8.5%, 95% CI 7.7%-9.3%) than those aged 12 years to 13 years (4%, 95% CI 3.4%-4.7%). Among adolescents who had ever had sex, the recent global prevalence of having multiple sexual partners was 52% (95% CI 50.4%-53.6%) and was higher among boys (58%, 95% CI 56.1%-59.9%) than girls (41.4%, 95% CI 38.9%-43.9%) and among those aged 14 years to 15 years (53.5%, 95% CI 51.6%-55.4%) than those aged 12 years to 13 years (49.7%, 95% CI 45.9%-53.5%). Among adolescents who had ever had sex, the recent global prevalence of condom use was 58.1% (95% CI 56.2%-59.9%) and was higher among girls (59.2%, 95% CI 56.4%-61.9%) than boys (57.7%, 95% CI 55.7%-59.7%) and among those aged 14 years to 15 years (59.9%, 95% CI 58.0%-61.8%) than those aged 12 years to 13 years (51.6%, 95% CI 47.5%-55.7%). Between the earliest and latest surveys, the overall prevalence of ever had sexual intercourse (3.1% decrease) and condom use (2.0% decrease) showed downward trends. The overall prevalence of having multiple sexual partners increased by 2.6%. ConclusionsWe provide evidence and important implication for policymakers to develop targeted policy support systems to prevent and reduce risky sexual behaviors among young adolescents in LMICs with a high prevalence of risky sexual behaviors.